2002
DOI: 10.1093/nar/30.3.643
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Rph1, a damage-responsive repressor of PHR1 in Saccharomyces cerevisiae, is dependent upon Rad53 kinase

Abstract: Rph1, a Cys2-His2 zinc finger protein, binds to an upstream repressing sequence of the photolyase gene PHR1, and represses its transcription in response to DNA damage in Saccharomyces cerevisiae. In this report, we have demonstrated that the phosphorylation of Rph1 protein was increased in response to DNA damage. The DNA damage-induced phosphorylation of Rph1 was missing in most damage checkpoint mutants including rad9, rad17, mec1 and rad53. These results indicate that Rph1 phosphorylation is under the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 31 publications
(43 reference statements)
1
15
0
Order By: Relevance
“…These data indicate that PHR1 induction is controlled by the Dunl-independent pathway for transducing the damage signal to Rphl-Gisl repressors (Sancar, 2000). In the previous report, we have demonstrated that Rphl was hyperphosphorylated by the Rad53-dependent checkpoint pathway but not by the Dunl protein kinase, supporting that the regulation of PHR1 expression by Rphl is not Dunl-de pendent (Kim et al, 2002).…”
Section: Dial Function Of Ag4 Sequence In Phu Promotersupporting
confidence: 60%
“…These data indicate that PHR1 induction is controlled by the Dunl-independent pathway for transducing the damage signal to Rphl-Gisl repressors (Sancar, 2000). In the previous report, we have demonstrated that Rphl was hyperphosphorylated by the Rad53-dependent checkpoint pathway but not by the Dunl protein kinase, supporting that the regulation of PHR1 expression by Rphl is not Dunl-de pendent (Kim et al, 2002).…”
Section: Dial Function Of Ag4 Sequence In Phu Promotersupporting
confidence: 60%
“…(Rfx1 was not examined because its phosphoregulation by Rad53 and Dun1 has been described by Huang et al (1998). Also note that Rph1, an additional TF included in Figure S1, has been shown to undergo Rad53-dependent, DNA damage-induced phosphorylation (Kim et al, 2002). ) The rad53Δ mutant was the focus of this analysis because virtually the entire checkpoint-kinase-mediated transcriptional response to MMS was Rad53 dependent (Figures 1C and 3C).…”
Section: Resultsmentioning
confidence: 99%
“…Rph1 negatively regulates the transcription of the photolyase gene PHR1 that mediates resistance to UV-induced DNA damage (37). Rph1 is also phosphorylated in a Rad53-dependent manner after DNA damage, which causes its dissociation from chromatin, thereby relieving repression of target genes (38). Given that Rph1 acts as an autophagy repressor (36) and is also linked to the DDR, we investigated whether Rph1 plays any role in ATG gene transcription after DNA damage.…”
Section: Gta Leads To Rad53-mediated Transcriptional Up-regulation Ofmentioning
confidence: 99%